Small shelly fauna from the upper Lower Cambrian Bastion and Ella Island Formations, North-East Greenland - Skovsted, Christian B. (2006)
A diverse and well-preserved fauna of shelly fossils from the upper Lower Cambrian Bastion and Ella Island Formations of North-East Greenland contains more than 90 species. The fauna is the most diverse shelly fauna yet discovered in the Lower Cambrian of Laurentia and includes many fossils previously known only from other continental blocks. It enhances correlation of the North-East Greenland succession into Laurentia, most notably with the Browns Pond Formation of New York State, but also with other important Early Cambrian continents, in particular with Australia, Antarctica, and Siberia. A middle Dyeran age is most probable for both the Bastion and Ella Island Formation, and the rich fossil assemblage facilitates correlation with the Botoman Stage of Siberia and its equivalents. One new taxon is described, the disc-shaped problematicum Tunudiscus duovittarius n. gen. and sp.